Evaluation of cultural competency in a South African cluster randomised controlled trial: lessons learned for trial reporting standards - Siegfried, NL; Hopewell, S; Erasmus-Claassen, L-A; Myers, B (BioMed Central, 2022)
Background Failure to consider relevant cultural, ethnic and diversity parameters (and the intersection between these parameters) during trial protocol development and trial conduct may negatively impact recruitment, intervention development and delivery, and participant adherence and retention, potentially reducing overall internal validity. This case study aimed to evaluate the utility and comparability between the 9-item Gibbs Framework to measure cultural competency and the GRIPP-2(Short Form (SF)) 5-point checklist to assess patient and public involvement in the context of a complex clinical trial conducted in an African setting.